Comparison of the adsorption behavior of melphalan anti-cancer drug on MgS nano-cage: A DFT study - Shahnaz Azari Gharelar; Shiva Masoudi; Nasrin Masnabadi; Mohammad Hadi Ghasemi (Results in Chemistry)
The adsorption behavior of melphalan anti-cancer drug on the MgS nano-cage surface was investigated using DFT and TD-DFT methods by B3LYP/6-31G(d) level of theory. From the obtained adsorption energies of MEL/MgS complexes (I-III), it was determined that the adsorption process is exothermic. The electrical conductivity of the MgS nanocage significantly increased in three complexes. Therefore, it can be used to generate electronic noise in the presence of MEL drug. The working functions of the most stable complex systems will be affected by the adsorption of the target drug. MgS nanocage is a ϕ-type sensor that can be active in the detection of MEL drug. Adsorption process of MEL on MgS nanocage as well as the structural changes after adsorption were studied by UV/Vis absorption, NCI and QTAIM analyses. The wavelength shift towards higher wavelengths in the electronic spectra of MEL/MgS complex indicates the binding and adsorption of MEL drug on MgS nanocage. To investigate the interaction mechanism between drug and adsorbent and also the changes in the properties of MEL drug and MgS nanocages, the geometric parameters, dipole moment, frontier molecular orbitals (FMO), and density of states (DOS), electron location function (ELF) and local orbital locator (LOL) were analyzed. Based on the studies conducted in this study, it can be argued that MgS nanocages with suitable electronic and structural properties can be considered as promising drug sensors for the drug MEL.